Alternative Treatment for Asthma: Case Study of Success of Traditional Chinese Medicine Treatment of Children from Urban Areas with Different Levels of Environmental Pollution. (9th August 2012) - Kopnina, Helen
Abstract : The present study examined efficacy of traditional Chinese medicine (TCM) treatment in Dutch children with asthma in areas with differing air pollution. The study results indicate that TCM treatment of children living in more polluted urban area is less successful then that of children living in cleaner air area.